New or rare Madagascar tiger beetles—18. Pogonostoma (Pogonostoma) ondravybirali sp. nov., elaborated redescriptions of P. (P.) atrorotundatum, P. (P.) densisculptum and P. (Microstenocera) fabiocassolai (Coleoptera: Cicindelidae) - Moravec, Jiří; Vybíral, Jan (Zootaxa, 2020)
Pogonostoma (Pogonostoma) ondravybirali sp. nov. from southwestern Madagascar is described as new to science. The new species is placed to a large P. (Pogonostoma) elegans species-group (sensu Moravec 2007) along with seven other mutually similar species which are recognized within this species-group as a species-complex of P. (P.) alluaudi W. Horn, 1898. An elaborated redescription of the most similar P. (P.) atrorotundatum W. Horn, 1934 is given. A revised key to the P. (P.) elegans species-group is presented in order to supplement the key in the monograph of the genus Pogonostoma Klug, 1835 by Moravec (2007). First description of male characters of P. (Pogonostoma) densisculptum Moravec, 2003 (belonging to P. (P.) gibbosum species-group sensu Moravec 2007) and first description of female characters of P. (Microstenocera) fabiocassolai Moravec, 2003 (of the P. (M.) minimum species-group sensu Moravec 2007) are introduced. Type and other specimens of the presented species are illustrated in colour photographs of their habitus, diagnostic characters and variability (including two diagnostic characters of P. (P.) gibbosum Rivalier, 1970). Essential maps of the distribution of the treated species in Madagascar are given.